Experimental Characterization of Traditional Plaster/ Cement Bricks for Building Applications: Physical and Mechanical Behaviour (Case of Ouargla) - Chaib, Hachem; Mokhtari, Abdsamed (International Journal of Sustainable Construction Engineering and Technology, 2024)
The aim of the work presented is to study the possibility of using traditional gypsum, which is found in considerable quantities in southern Algeria, to prepare bricks with sufficient mechanical characteristics to qualify them for the various applications and uses in construction. The improvement of the mechanical properties of traditional gypsum was carried out in two phases: The first phase by adding ordinary Portland cement with different mass ratios of 0, 1, 2, 3, 4 and 5%. The results showed that the addition of 2% of (OPC) gave the best value to make the bricks more resistant. The second phase is to study the durability and knowledge of the effect of water on traditional plaster bricks and (OPC). After determining the best C2 sample of 98% traditional plaster and 2% (OPC), these samples were placed in drinking water baths and the others in aggressive water baths in 7 days, 14 days, 21 days, 28 days, 60 days and 90 days. After applying the mechanical tests of all the samples on the specified dates, it was found that the mechanical results increased with time.